2000
DOI: 10.1086/314041
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Characterization of Adenovirus 5 from the Brain of an Infant with Fatal Cerebral Edema

Abstract: This report describes a fatal case of cerebral edema caused by adenovirus in a previously healthy 18-month-old infant who developed skin rash, pulmonary congestion, and fever and who died 6 days later. Adenovirus hexon gene sequences were detected in brain tissue and brain tissue cultures. The virus was typed as adenovirus 5.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 11 publications
0
13
0
Order By: Relevance
“…A 20.4 K gene product is homologue to the pVII, and a predicted product of 7.9 K represents the pX protein of HAdV-A31. All three proteins are described as being core proteins and are associated with the virus DNA [48]. The sequence generated for pX protein of HAdV-A31 was highly divergent from the HAdV-A31 pX sequence previously available in GenBank [GenBank: U14653] (nucleic acid sequence homology 70.4%, amino acid 53.4%).…”
Section: Resultsmentioning
confidence: 99%
“…A 20.4 K gene product is homologue to the pVII, and a predicted product of 7.9 K represents the pX protein of HAdV-A31. All three proteins are described as being core proteins and are associated with the virus DNA [48]. The sequence generated for pX protein of HAdV-A31 was highly divergent from the HAdV-A31 pX sequence previously available in GenBank [GenBank: U14653] (nucleic acid sequence homology 70.4%, amino acid 53.4%).…”
Section: Resultsmentioning
confidence: 99%
“…Although adenovirus types 5 and 21 are associated with novel strains [49], epidemics [33,34,50,51], severe disease [52], and death [53], these observations have been relatively rare. Our data revealed that, of the 13 patients with adenovirus infection who died, 1 had been be associated with more frequent or more severe disease, as well as the unexpected lack of such associations with adenovirus type 7, merit further molecular investigation to determine whether there are viral predictors of disease severity.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, there have been no previous reports on the systematic investigation of the entire spectrum of AdVs in the brain covering both malignant and nonmalignant tissue. Although brain tissue tropism has been previously described for murine AdV type 1 in a mouse model (22), only a small number of case reports describing the occurrence of AdV in the human brain have been published to date (5,14). The screening data presented in this study provide new insights into AdV infection of cerebral tissue and the brain as a potential sanctuary for virus persistence and raise questions about the possible involvement of these viruses in the pathogenesis of brain tumors.…”
Section: Discussionmentioning
confidence: 99%